A new model for beam crack detection and localization using a discrete model. (1st November 2017) - Khnaijar, Ahmed; Benamar, Rhali
Highlights: Establishment of a new discrete model for cracked beams. Validation of the crack model for various end conditions, i.e. simply supported, clamped and cantilever beams. Application of the model to the crack detection procedure. Abstract: This paper presents a new discrete physical model to approach the problem of cracked beam vibrations. The model consists of a beam made of several small and evenly spaced bars. The beam bending stiffness is modeled by spiral springs that serve also as a crack model. Concentrated masses presenting the inertia of the beam are located at the bar ends. This model has the advantage of simplifying parametric studies, because of its discrete nature, allowing easy modification in the crack position and magnitude. Therefore, once the model is established, various practical applications may be performed without the need to go through all the formulations again. As a result, this model allows conducting a parametric study with the objective of facilitating the diagnostics process involving both crack localization and depth estimation.